Some tribal medicinal plants of Chittagong Hill Tracts, Bangladesh - Yusuf, Mohammed; Wahab, MA; Yousuf, Md; Chowdhury, Jasim Uddin; Begum, Jaripa (Bangladesh Journal of Plant Taxonomy, 2007)
A survey was carried out in different localities of Rangamati and Bandarban Districts of Bangladesh between 2001 and 2002 to document medicinal plants. A total of 69 medicinal plants under 40 families were documented during this work, which the tribal use to treat about 50 diseases. Scientific names, tribal names of the plants, parts used, names of the diseases and names of the user communities are mentioned. Key words: Hill Tracts, Medicinal plants, Traditional knowledge, Bangladesh DOI: 10.3329/bjpt.v14i2.531 Bangladesh J. Plant Taxon. 14(2): 117-128, 2007 (December)